Innovative and Biodegradable Sanitary Napkins with Focus on Affordability and Environmental Impact - Chavan, Shivani P.; Wankhade, Rahul G.; Kharat, Mayur G.; Khandarkar, Shivali M.; Kulkarni, Vedangi A.; Mhaske, Shivshankar D.; Nagrik, Shatrughna U. (Journal for Research in Applied Sciences and Biotechnology, 2024)
The awareness people have towards the environment pollution resulting from the use of the normal sanitary napkins has encouraged production of eco-friendly napkins. Modern ones are largely plastic-wired sanitary napkins constructed with superabsorbent polymers as their major components, which take roughly 500 years to degrade. This presents a major environmental concern, seeing that each woman will use about 11,000 pads in their lifetime and these are bound to a landfill. As a remedy the sanitary napkins that are biodegradable has been developed using banana fiber, bamboo, and polylactic acid derived from cornstarch. The current paper seeks to establish the possibility to use these environmentally friendly products with special emphasis on the cost issues and the impact they would have on the environment. Low cost, high biodegradability, high absorbency, high tensile strength, and possibility for banana fiber in the development region are pointed out. The outcome in terms of banana fiber sheets production as well as their incorporation into Sanitary Napkin were encouraging in respect of absorbency, antibacterial activity and biodegradability. The tests proved that the new biodegradable napkins disintegrate much more quickly than current plastic-based products, in a matter of months, contrary to the centuries that it would take for plastic pads to decompose. This is the reason why current biodegradable napkin products cost more than conventional napkin products as production price is still relatively high; however, measures of procuring locally and constantly improving material processing to manage the cost down are in the works. This research adds for the possibility of biodegradable sanitary napkin to reduce environmental degradation, through the alternative provision of safe and affordable, hygienic menstrual solutions where there are few to non-existent. Such products if further developed and marketed on large scale could be made available and sustainable for people all over the world.